MOTIVATION, INDEPENDENCE, INTEREST IN LEARNING AND LEARNING METHODS TO THE LEARNING ACHIEVEMENTS OF STUDENTS OF SMA BATIK 2 SURAKARTA - Dwi Harjanto; Istiatin Istiatin; Sarsono Sarsono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to determine the simultaneous and partial influence of motivational variables, independence, learning interests, and learning methods on students' learning achievements at SMA Batik 2 Surakarta. This research method uses a quantitative descriptive research design. The population of all grade XI students of SMA Batik 2 Surakarta amounted to 285 people, with a sample number of 70 students. Sampling techniques using purposive sampling. Data collection using questionnaires. Data analysis techniques using statistical analysis are multiple linear regression tests, F tests, t-tests, and determination coefficients. The results showed that motivation, independence, interest in learning, and learning methods influenced students' learning achievement by 81.0% while 19.0% was influenced by other variables that were not conscientious, such as discipline, education level of parents, peers and others. The suggestion of this research is that SMA Batik 2 Surakarta should always increase motivation, independence, interest in learning and learning methods in order for students' learning achievements to improve from before.